On the p-Version of the Schwab-Borchardt Mean - Edward Neuman (International Journal of Mathematics and Mathematical Sciences)
This paper deals with a one-parameter generalization of the Schwab-Borchardt mean. The new mean is defined in terms of the inverse functions of the generalized trigonometric and generalized hyperbolic functions. The four new bivariate means are introduced as particular cases of the p-version of the Schwab-Borchardt mean. For the particular value of the parameter p, these means become either the classical logarithmic mean or the Seiffert means or the Neuman-Sándor mean. Wilker- and Huygens-type inequalities involving inverse functions of the generalized trigonometric and the generalized hyperbolic functions are also established.